SISTEM INFORMASI PENGUMPULAN DATA LISTING PROPERTI BERBASIS WEB (EDWIN BRIGHT PROPERTY) - Dimas Muhammad Yusup; Deni Dwi Rifa'i; Muhammad Rifqi Juniawan; Sutriyono (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
Competition for property agents continues to increase every year. Edwin Bright Property as a property agent in data collection is still fairly manual. With these problems, a web-based property agent information system research was carried out using the programming languages PHP, MySQL, HTML, CSS and Javascript. The research resulted in a web-based property agent application that can run well in mobile and desktop mode browsers. that way property agents can serve clients quickly and precisely.